Comparison of high-performance liquid chromatography of cyclotriphosphazene derivatives with one or two equivalent stereogenic centres - Besli, Serap; Davies, David B.; Kilic, Adem; Shaw, Robert A.; Sahin, Sule; Uslu, Aylin; Yeşilot, Serkan (Elsevier, 2006)
High-performance liquid chromatographic (HPLC) methods have been developed for investigating the stereogenic properties of two analogous series of dibenzylamino derivatives of cyclotriphosphazene containing either one or two equivalent stereogenic centres. Separation of the enantiomers of all the racemic compounds has been investigated by chiral HPLC using Whelk-01 and Chiralcel OD columns. In all cases, conditions for separation of enantiomers have been found using a Whelk-01 column with different ratios of tetrahydrofuran in n-hexane as the mobile phase. It is found that both the separation factor (alpha) and resolution factor (R-S) of molecules with two equivalent stereogenic centres are greater than those for analogues with only one centre. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: enantiomers; chiral HPLC; whelk-01 column; cyclotriphosphazene derivatives